Evaluation Of The Deaths Due To Electrical Currents Which Performed Autopsies Between 2007-2014 Years In Diyarbakır - Korkmaz, Mustafa; Uysal, Cem (The Bulletin of Legal Medicine, 2021)
Objective: Electrical current injuries are an important cause for mortality and morbidity; and they may be prevented by simple precautions in general. The present study aimed to review the cases of death due to electrical current in ... region between 2007 and 2014. Material and Methods: We analyzed 6341 forensic death reports retrospectively in the present study. The present study included 239 (3.77%) deceased individuals who dies because of electrical current injury. Age, gender, origin of death, the crime scene, location of electric entrance and exit on the body were reviewed. Findings: The cases included 147(61.5%) males, 92(38.5%) females and the age average was 23.15+17.1 years (min:1,max:78). All deaths due to electrical current were accidental. Death cases were detected more common during summer season. The most common contact site was the upper extremity which was detected in 112 (46.9%) cases. There were 34 cases (14.2%) without any electrical burn scar. Seventy six (46.6%) cases died because of home accidents. The most significant findings of our study were that 114 (47.7%) cases were between 0 and 18 years of age and electric water heaters were the cause of the incident in 33 (28.9%) cases. Conclusion: Among all forensic death cases of the present study, rate of death due to electric shock were found higher wen compared with the previous studies. Rate of pediatric deaths due to electric shock was found higher in the present study. Therefore, individuals should be trained to avoid the children to play with household electric appliances.